(untitled) (Academicia Globe: Inderscience Research, 2022)
So far, people have used repetition in many different and very complex ways. People have been using these methods for a long time, but with the advent of the Internet, very convenient and fast search methods have appeared. In the 21st century, that is, in the age of information technology, each user has his own profession, and it is widely used by representatives of all spheres of the world, artisans, merchants.